2019
DOI: 10.1097/aog.0000000000003091
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Cesarean Delivery Surgical Site Infections

Abstract: Objective: To examine the association of a resident-driven quality initiative with cesarean delivery surgical site infections. Methods: This was a quasi-experimental, preintervention and postintervention study of women undergoing cesarean delivery at 23 weeks of gestation or greater between January 2015 and June 2018 at a single tertiary care center. We implemented a resident-driven, evidence-based surgical bundle, excluding women who underwent emergency cesarean or had chorioamnionitis. The bundle included ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…In a different study of a bundled approach to reducing SSIs (including both azithromycin and vaginal cleansing along with other measures), a benefit of approximately 50% lower rates was achieved. 21 Nonetheless, in the present study, a reduction in infection rates of a similar magnitude (50%) occurred without broadening the antimicrobial spectrum. This latter finding is important because of the risks inherent in antibiotic use.…”
Section: Discussionsupporting
confidence: 57%
“…In a different study of a bundled approach to reducing SSIs (including both azithromycin and vaginal cleansing along with other measures), a benefit of approximately 50% lower rates was achieved. 21 Nonetheless, in the present study, a reduction in infection rates of a similar magnitude (50%) occurred without broadening the antimicrobial spectrum. This latter finding is important because of the risks inherent in antibiotic use.…”
Section: Discussionsupporting
confidence: 57%
“…Both Lemming et al and Kawakita et al reported a more than 50% reduction in surgical site infection when either four or nine aspects of cesarean delivery preparation or technique were standardized, respectively. 9 , 10 In a systematic review and meta-analysis of 44 studies, Martin et al 11 found similar surgical site infection reduction when preoperative antibiotic prophylaxis, vaginal preparation and spontaneous removal of the placenta were standardly performed. Carter et al 12 also demonstrated that evidence-based bundles were associated with reduced surgical site infection in a systematic review and meta-analysis.…”
Section: Why Standardize Cesarean Delivery Surgical Technique?mentioning
confidence: 97%
“…In a recent study conducted by Ramesar et al in a South African private hospital, it was demonstrated that implementing a surgical care pathway helped to reduce the incidence of surgical site infections in caesarean section deliveries. 21 The study initially mapped out the surgical journey of these patients from admission to discharge and then conducted an audit using a scoring system regarding compliance to the CDC guidelines for the prevention of surgical site infections. 21 Once key areas of non-compliance were identified, performance improvement protocols were implemented which saw infection rates reduce from 5.12±0.82% to 0.23±0.15% (p<0.0001) in as little as 30 days.…”
Section: Surgical Care Pathwaysmentioning
confidence: 99%
“…21 The study initially mapped out the surgical journey of these patients from admission to discharge and then conducted an audit using a scoring system regarding compliance to the CDC guidelines for the prevention of surgical site infections. 21 Once key areas of non-compliance were identified, performance improvement protocols were implemented which saw infection rates reduce from 5.12±0.82% to 0.23±0.15% (p<0.0001) in as little as 30 days. 21 The COVID-19 pandemic has wreaked havoc across the globe by crashing economies and devastating healthcare systems even in the most well-resourced and technologically advanced countries.…”
Section: Surgical Care Pathwaysmentioning
confidence: 99%